SOSIALISASI PENTINGNYA PEMANFAATAN ARTIFICIAL INTELLIGENCE DALAM DUNIA PENDIDIKAN DI SMA NEGERI 1 PADANG BOLAK - Pohan, Rizky Febriani; Rambe, Muhammad Rahman; Nasution, Alvi Sahrin (FORDICATE, 2025)
The problems faced by teachers and students of SMA Negeri 1 Padang Bolak related to the use of artificial intelligence (AI) are social problems, namely the lack of knowledge and skills in applying artificial intelligence (AI) in learning and management problems, namely the lack of school facilities in the form of digital computers that apply artificial intelligence (AI). The method used to overcome these two problems is the socialization method. The aim is to improve the knowledge and skills of teachers and students of SMA Negeri 1 Padang Bolak in utilizing artificial intelligence (AI) in the teaching and learning process. The results of the activity show that artificial intelligence (AI) technology has a significant influence on increasing knowledge and skills in utilizing artificial intelligence (AI) for learning needs. The increase in knowledge and skills of teachers of SMA Negeri 1 Padang Bolak in utilizing artificial intelligence (AI) in learning was 51.22%. Meanwhile, the increase in knowledge and skills of students of SMA Negeri 1 Padang Bolak in utilizing artificial intelligence (AI) in learning was 37.17%.